Pengaruh Tax Planning, Financial Distress, dan Total Asset Turnover terhadap Kinerja Perusahaan yang Dimoderasi oleh Kegiatan Research and Development - Tambun, Sihar (Media Akuntansi Perpajakan, 2021)
This study aims to examine the effect of Tax Planning, Financial Distress, and Total Asset Turnover on Company Performance as moderated by Company Development Research Activities. This research proxies Company Performance with Return On Equity, Tax Planning is proxied by Effective Tax Rate, Financial Distress is proxied by the discriminant function of the Altman Z-Score model, Total Asset Turnover is proxied by the formula for measuring the ratio of net sales to total assets, and Company Development Research Activities are proxied by the formula R&D (Research and Development). This study uses secondary data using documentation data collection and literature study on the Indonesia Stock Exchange website (www.idx.co.id) in the form of annual financial reports. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019 with the sampling technique using purposive sampling method.The results of this study indicate that Tax Planning has a positive and insignificant effect on company performance. This means that maximum tax planning does not necessarily result in good company performance, Financial Distress has a significant positive effect on Company Performance, Total Asset Turnover has a negative and insignificant effect on Company Performance, Research and Development has a negative and insignificant effect on Company Performance, R&D is able to strengthen the influence. Tax Planning on Company Performance, R&D is able to strengthen the influence of Financial Distress on Company Performance, R&D is able to strengthen the effect of Asset Turnover on Company Performance.Keywords: Tax Planning, Financial Distress, Asset Turnover, Company Performance, Company Research and Development.